Lifestyle and Psychological Factors Affecting Eating Habits and Physical Activity Among Government Servants in the States With the Highest Cumulative Cases in Malaysia During the COVID-19 Pandemic - Hamzaid, Nur Hana; Gumisi, Zeesha Gloria Rayner; Ahmad Helme, Syaidatul Khafizah; Azmi, Norhazirah; Shahril, Mohd. Razif (Frontiers in Public Health, 2022)
Introduction: Like many countries, the federal government of Malaysia took the initiative to implement nationwide home confinement as a preventive measure in response to the pandemic COVID-19 outbreak, better known as Movement Control Order (MCO). Many have suffered economically, which leads to pr states of well-being. This study investigates the relationship between lifestyle, psychological factors affecting eating habits, and physical activity among government servants in states with the highest cumulative cases during the COVID-19 pandemic. Methods: A cross-sectional online survey was conducted among 210 government servants from four states (Selangor, Sabah, Kuala Lumpur, and Johor) from May 2021 to June 2021. Three validated questionnaires were used; López-Moreno et al. 2020, Emotional-Eater Questionnaire (EEQ), and Malay International Physical Activity Questionnaire (IPAQ-M). Results: There were significant gender differences (p < 0.001) for supplement intake (30.4% men and 62.3% women). Almost half (49.1%) were classified as emotional or very emotional eater. Also a significant differences (p < 0.005) in the perception of boredom and apathy between men (35.7%) and women (31.8%). A majority (56.2%) stated that their mood positively affected their eating habit. The total MET for 132 subjects was 3495.8 ± 3862.7 minutes/week for physical activity. Significance differences were observed between MET and gender (Mann-Whitney U test: p = 0.019), with men showing higher MET value (5001.4 ± 5354.0 min/week men, 2864.3 ± 2754.3 min/week women). A significant difference was observed among women for body weight and BMI before and during MCO (p < 0.001). For the emotional eater, there were correlations with eating habits before the MCO for quantity of food intake (p = 0.003), frequency of mealtime (p < 0.001), changes of food habits (p = 0.005), cooking methods (p = 0.016), and frequency of food intake (p = 0.020). There is no correlation (p = 0.577) between psychological factors affecting eating habits and physical activity during COVID-19. Conclusion: Changes were reported before and during MCO on lifestyle, eating habits, and physical activity. Such information will help design strategies to improve the economic and health status among government servants in Malaysia during the implementation of MCO or something similar.